2004
DOI: 10.1079/phn2003532
|View full text |Cite
|
Sign up to set email alerts
|

Successful strategies to increase the consumption of fruits and vegetables: results from the Danish ‘6 a day’ Work-site Canteen Model Study

Abstract: Objective: To investigate changes in the consumption of fruits and vegetables in worksite canteens using the tools of continuous quality improvement, and to gain knowledge of practical strategies being effective in increasing the consumption. Design: Study design included baseline data collection, an 8 h training session for all canteen staff, goal setting, strategy development and implementation for each canteen, end-point data collection and a follow-up data collection 4 months from the end-point (1 year fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
89
0
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(97 citation statements)
references
References 27 publications
2
89
0
6
Order By: Relevance
“…The study also showed that the effects of the intervention persisted for 4 months after the intervention end-point (15) .…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The study also showed that the effects of the intervention persisted for 4 months after the intervention end-point (15) .…”
Section: Discussionmentioning
confidence: 73%
“…Other studies also observed that the inclusion of vegetables is easier with warm preparations such as a side dish (15,27) . Emphasizing that as a strategy of intervention, in the present study the culinary workshop's special focus was given to the preparation and presentation of vegetables on the menus offered.…”
Section: Discussionmentioning
confidence: 90%
“…*Number of days of monitoring at each canteen. in the canteens by giving access to tasteful and healthy food choices and reducing the availability of unhealthy options (16) . We believe that some of the key elements for sustaining this tailored intervention were management involvement, empowering the canteen staff, getting everyone in the canteen involved in a proactive way and providing networking opportunities between canteen managers.…”
Section: Baseline Intakementioning
confidence: 99%
“…Even though the worksite canteens seem to be a promising setting for promoting healthy eating (26,(34)(35)(36) , there is limited knowledge on how healthy eating can be promoted most effectively at the workplace. Taking into account that previous studies (23,32,33,37) have found that meals consumed outside the home can make a significant contribution to the fat content of the diet, it is important that the daily meals at the worksite canteen comply with minimum nutritional recommendations.…”
Section: Discussionmentioning
confidence: 99%